Thickness homogenization method for magnesium-aluminum alloy self-special-shaped layered hydrothermal film
By using a single sodium hydroxide solution system on the surface of the magnesium aluminum alloy for hydrothermal treatment, combined with solid solution and aging treatment, the second phase is refined, and the thickness uniformization of the self-special-shaped layered hydrothermal film of the magnesium aluminum alloy is achieved, solving the problems of complex processes and uneven thicknesses in the prior art, and achieving green and environmentally friendly film layer preparation.
Patent Information
- Application Number
- CN202411780917.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The preparation process of LDH film layer on the surface of magnesium alloy is complex, the solution composition is complex, and it may involve hazardous chemicals, and the in-situ growth of the hydrothermal film layer is caused by the uneven thickness caused by the second phase in the matrix.
A single sodium hydroxide solution system was used for hydrothermal treatment. By adjusting the concentration of the hydrothermal solution, a self-specially shaped layered hydrothermal film was obtained. The inner layer was a dense magnesium hydroxide layer and the top was a layered sheet-shaped LDH layer. Through solid solution and aging treatment, the second phase is refined and evenly dispersed in the grains to avoid uneven thickness of the hydrothermal film.
The thickness uniformization of the self-specially shaped layered hydrothermal film of magnesium-aluminum alloy is achieved, avoiding the problem of uneven thickness of the hydrothermal film caused by the second phase. It also adopts a simple sodium hydroxide solution system, which is green and environmentally friendly and does not involve hazardous chemicals.
Smart Images

Figure CN119592889A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, and in particular relates to a method for uniformizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film. Background Art
[0002] With the development of society, energy issues are becoming more and more prominent. Controlling the weight of structural parts can reduce energy consumption. As one of the lightest structural metals, magnesium alloy has the characteristics of low density, high specific strength and good biocompatibility. It is widely used in automobiles, civil engineering, 3C products and biomedical fields. However, the poor corrosion resistance of magnesium alloy itself limits its long-term service, especially in aqueous solutions containing chloride ions. Layered double hydroxide (LDH) is a special type of layered material. Its upper and lower layers are composed of positively charged mixed metal hydroxide layers, separated by anions and water molecules in the middle, and maintain charge balance. The interlayer anions can exchange with anions in the external environment, thereby capturing corrosive ions in the environment (such as Cl - ions), thereby slowing down the corrosion rate. The preparation methods of LDH film on the surface of magnesium alloy usually include co-precipitation method, electrochemical deposition method, in-situ growth method, etc.
[0003] Patent CN108707889A introduces a method for in-situ growth of LDH conversion film on magnesium alloy, using hydrothermal conversion treatment solution of aluminum nitrate, sodium carbonate, sodium hydroxide and ammonium nitrate to construct a bird's nest-like LDH structure on the surface of magnesium alloy. Patent CN117187805A introduces a two-step co-precipitation method for preparing LDH film. First, magnesium hydroxide precursor is prepared by hydrothermal method, and then Mg 2+ and Al 3+The co-deposition solution was used to successfully prepare the LDH film layer. Patent CN110484950A introduces a method for preparing the LDH film layer by electrodeposition. The electrodeposition solution used is mainly divalent nitrate, trivalent nitrate, sodium nitrate and potassium nitrate. The co-precipitation method and electrodeposition method are complicated, and the prepared LDH film layer has poor bonding with the substrate. The hydrothermal method has the advantages of simple operation, green and environmentally friendly hydrothermal solution, and strong film bonding, and has been favored by researchers. Zhang et al. (DOI: 10.1038 / srep17399) and Wu et al. (DOI: 10.1016 / j.apsusc.2019.01.181) proposed a hydrothermal-based in-situ growth method. Through a one-step hydrothermal treatment, a self-heteromorphic stratified hydrothermal film was obtained, that is, the top layer of the hydrothermal film was a lamellar LDH, and the inner layer was a dense magnesium hydroxide film. The use of this hydrothermal film with a composite structure can achieve surface corrosion protection and functional integration of magnesium alloys. However, the in-situ growth hydrothermal method of magnesium alloys is greatly affected by the microstructure of the matrix. For example, in cast Mg-Al alloys, the second phase (Mg 17 Al 12 ) and the thickness of the film grown on the substrate are often quite different, so the problem of uniform thickness of the hydrothermal film needs to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a method for uniformizing the thickness of a self-shaped stratified hydrothermal film of a magnesium-aluminum alloy. The present invention aims to solve the complex preparation process of the LDH film layer on the surface of the current magnesium alloy, especially the complex composition of the preparation solution and the possibility that some nitrates are hazardous chemicals, as well as the problem of uneven thickness of the in-situ grown hydrothermal film layer caused by the second phase in the matrix.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film, comprising the following steps:
[0007] Pretreatment of magnesium-aluminum alloy;
[0008] The pretreated magnesium-aluminum alloy is buried in graphite powder for solution treatment, and a first water cooling treatment is performed after the solution treatment is completed;
[0009] The product after the first water cooling treatment is buried in graphite powder again for aging treatment, and a second water cooling treatment is performed after the aging treatment is completed;
[0010] Grinding, cleaning and drying the product after the second water cooling treatment;
[0011] A sodium hydroxide solution with a concentration of 0.01 M is added to the dried product for hydrothermal treatment, and the product after the hydrothermal treatment is cleaned and dried.
[0012] The present invention adopts a single sodium hydroxide solution system, the solution components are simple, green and less polluting, and does not involve the use of hazardous chemicals. By adjusting the concentration of the hydrothermal solution-sodium hydroxide solution, a self-shaped stratified hydrothermal film is obtained, that is, a composite film with a dense magnesium hydroxide layer as the inner layer and a lamellar LDH layer as the top. The second phase with different shapes and sizes is obtained by heat treatment. The refined second phase is evenly dispersed in the grains, so that the obtained hydrothermal film layer avoids the uneven thickness of the hydrothermal film caused by the second phase.
[0013] Preferably, the step of pre-treating the magnesium-aluminum alloy is: washing the magnesium-aluminum alloy with soapy water, deionized water and anhydrous ethanol in sequence, and drying. Soapy water has a strong decontamination ability and can effectively remove grease, dust and other stains on the surface of the magnesium-aluminum alloy. Compared with some strong acid or strong alkali cleaning agents, soapy water is milder and will not cause serious corrosion or damage to the surface of the magnesium-aluminum alloy. After washing with soapy water, some soap components or other stains may remain on the surface of the magnesium-aluminum alloy. Using deionized water for washing can remove these residues and make the alloy surface cleaner. After washing with deionized water, the surface of the magnesium-aluminum alloy will be in a relatively clean state, which is conducive to the subsequent washing and drying with anhydrous ethanol. Anhydrous ethanol has a strong volatility and can quickly take away the moisture on the surface of the magnesium-aluminum alloy to avoid corrosion or oxidation caused by residual moisture. Ethanol also has a certain degreasing effect, which can further remove grease and other stains on the surface of the alloy and make the surface cleaner. The volatility of anhydrous ethanol helps to speed up the drying speed of the magnesium-aluminum alloy and shorten the processing time. After cleaning with soapy water, water and anhydrous ethanol in sequence, the surface of the magnesium-aluminum alloy will be cleaner and smoother, which is beneficial to improving the overall quality and performance of the alloy. The cleaning process of the present invention avoids the use of strong acid or strong alkali cleaning agents, reduces the risk of corrosion on the alloy surface, and the surface of the magnesium-aluminum alloy after cleaning is more suitable for subsequent processing steps. In summary, cleaning the magnesium-aluminum alloy with soapy water, deionized water and anhydrous ethanol in sequence is an effective surface treatment method, which can significantly improve the surface quality and performance of the alloy, and lay a good foundation for subsequent processing steps.
[0014] Preferably, the temperature of the solution treatment is 410°C and the holding time is 24 hours. Solution treatment is an important metal heat treatment process, which can reduce the amount of the second phase and reduce its size. 17 Al 12It is the most important second phase. A large amount of aluminum is enriched in the second phase. Aluminum is easy to form a dense oxide film during corrosion, which acts as a corrosion barrier. Therefore, the second phase is not easily corroded during the corrosion process. On the other hand, Mg 17 Al 12 The potential of the second phase is higher than that of the substrate, and it is easy to form a corrosion microcouple with the substrate, accelerating the corrosion of the substrate. Hydrothermal treatment can be considered as a special form of corrosion under high temperature and high pressure conditions. The difference in corrosion resistance between the second phase and the substrate will lead to differences in the thickness of the hydrothermal film layer. Therefore, reducing the number of coarse island-like second phases in the original cast sample and reducing its size through solution treatment will be beneficial to the formation of a uniform hydrothermal film layer. In addition, through a certain holding time, the aluminum element in the second phase can be diffused into the matrix, which is beneficial to the uniform precipitation and distribution of the second phase during the aging process. In the present invention, the best solution treatment effect can be obtained when the solution treatment temperature is 410°C and the holding time is 24h.
[0015] Preferably, the temperature of the aging treatment is 300°C and the holding time is 12h. The temperature and time of the aging treatment have a huge impact on the microstructure of the magnesium-aluminum alloy. In magnesium-aluminum alloys, there are usually two types of precipitation phases, one is discontinuous precipitation and the other is continuous precipitation. Discontinuous precipitation phases usually precipitate at lower aging temperatures, often alternating with α phases to form (α+β) flakes. Continuous precipitation phases usually precipitate at higher aging temperatures and present independent lamellar shapes. However, since the lower aging temperature limits the precipitation ability of the discontinuous precipitation phase, it usually appears near the grain boundary and the residual second phase. When the aging temperature rises, a large amount of continuous precipitation phase will precipitate inside the grain. The uniformly distributed second phase can transform severe local corrosion into uniform corrosion on the entire surface, thereby playing a role in homogenizing the thickness of the hydrothermal film layer. Therefore, in the present invention, a higher aging treatment temperature of 300°C is selected and kept warm for 12h to ensure full precipitation of the second phase.
[0016] Preferably, the polishing is: polishing with 800#, 1200# and 2000# SiC sandpaper in sequence. The particles of 800# SiC sandpaper are relatively coarse, and can quickly remove larger defects on the surface of the magnesium-aluminum alloy, such as oxide layer, scratches, protrusions, etc. Through rough polishing, the alloy surface can be initially smoothed, laying the foundation for subsequent polishing steps. The particles of 1200# and 2000# SiC sandpaper are finer than 800# SiC sandpaper, and can further remove minor defects on the surface of the alloy, such as small scratches and unevenness. After polishing with 2000# SiC sandpaper, the surface of the alloy will become smoother and more delicate, preparing for the subsequent hydrothermal treatment. In short, polishing with 800#, 1200# and 2000# SiC sandpaper in sequence can not only effectively remove various defects on the surface of the magnesium-aluminum alloy, but also make its surface smoother and more delicate, thus preparing for hydrothermal treatment.
[0017] Preferably, the temperature of the hydrothermal treatment is 120°C, and the holding time is 10 hours. The temperature and time of the hydrothermal treatment have an important influence on the thickness of the hydrothermal film layer. The higher the reaction temperature, the faster the crystal growth rate, the thicker the film layer, and the corrosion resistance of the hydrothermal film is proportional to its thickness, that is, the thicker the thickness, the better the corrosion resistance. As the hydrothermal reaction time increases and the hydrothermal film layer continues to thicken, dissolution and precipitation reach a balance, and the hydrothermal film layer will no longer grow. At the same time, protected by the hydrothermal film, the matrix no longer dissolves to provide magnesium ions. Therefore, the time of the hydrothermal treatment should not be too long. The present invention comprehensively considers the time cost and efficiency issues, and finally selects a hydrothermal treatment temperature of 120°C and a holding time of 10 hours.
[0018] In the method of the present invention, the solution during the hydrothermal treatment is a 0.01M sodium hydroxide solution with a pH of 12. The pH of the solution during the hydrothermal treatment has an important influence on the formation of LDH and the thickness of the hydrothermal film layer. When the pH is too high, for example, when the pH is equal to 14, a thick and dense magnesium hydroxide hydrothermal film can be formed, but there will be no self-decomposition phenomenon, that is, LDH will not appear on the surface; when the pH is relatively low, the solution is acidic, which will cause destructive corrosion to the sample. Therefore, the present invention preferably uses a 0.01M sodium hydroxide solution with a pH of 12 as the solution during the hydrothermal treatment.
[0019] Preferably, the drying is cold air drying. In the sample pretreatment stage, cold air drying can reduce the possibility of oxidation on the magnesium alloy surface, and in the hydrothermal treatment stage, cold air drying can reduce the possibility of cracking and oxidation of the hydrothermal film layer due to temperature difference.
[0020] More preferably, the method for homogenizing the thickness of the magnesium-aluminum alloy self-shaped layered hydrothermal film is:
[0021] (1) Sample pretreatment
[0022] 1) Cleaning: First, clean the magnesium-aluminum alloy with soapy water to remove surface oil, then rinse with deionized water, and finally ultrasonically clean in anhydrous ethanol for 5 minutes;
[0023] 2) Drying: Take the magnesium-aluminum alloy out of the anhydrous ethanol and blow dry it with cold air;
[0024] (2) Heat treatment:
[0025] The box furnace is heated to 410°C, the magnesium-aluminum alloy is buried in graphite powder and compacted to isolate the air, and then placed in the box furnace for solid solution treatment. After keeping warm for 24 hours, it is taken out and water-cooled. The sample after solid solution is buried in graphite powder again and placed in the box furnace for aging treatment. The aging temperature is 300°C, the insulation time is 12 hours, and then it is taken out and water-cooled to achieve the purpose of adjusting the microstructure.
[0026] (3) Hydrothermal treatment:
[0027] 1) Grinding: Grind the heat-treated samples with 800#, 1200# and 2000# SiC sandpaper in turn to smooth the surface and remove the oxide layer formed by heat treatment;
[0028] 2) Cleaning: Rinse the polished sample with deionized water first, and then ultrasonically clean it with anhydrous ethanol for 5 minutes;
[0029] 3) Drying: Take the sample out of the anhydrous ethanol and blow dry it with cold air;
[0030] 4) Hydrothermal reaction: Place the prepared sample in a polytetrafluoroethylene liner, add 10 mL of 0.01 M sodium hydroxide solution, seal it in a stainless steel hydrothermal kettle, place it in a forced air drying oven, heat it to 120 ° C and keep it warm for 10 h, then take it out;
[0031] 5) Cleaning: First, rinse off the hydrothermal solution remaining on the surface with deionized water, and then rinse with anhydrous ethanol;
[0032] 6) Drying: Finally, use cold air to blow dry the anhydrous ethanol.
[0033] Compared with the prior art, the present invention has the following advantages and technical effects:
[0034] The present invention discloses a method for homogenizing the thickness of a self-shaped stratified hydrothermal film of a magnesium-aluminum alloy based on a hierarchical structure of a precipitated phase. Compared with the solution components of a conventional co-deposition method, an electrodeposition method, etc., the method of the present invention adopts a single sodium hydroxide solution system, and the solution components are simple, green, and less polluting, and does not involve the use of hazardous chemicals. By adjusting the concentration of the hydrothermal solution-the sodium hydroxide solution, a self-shaped stratified hydrothermal film is obtained, that is, a composite film with a dense magnesium hydroxide layer as the inner layer and a lamellar LDH layer as the top. A second phase of different shapes and sizes is obtained by a heat treatment method, and the refined second phase is evenly dispersed in the grains, so that the obtained hydrothermal film layer avoids the uneven thickness of the hydrothermal film caused by the second phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0036] Figure 1 The SEM microstructure of the as-cast sample in Example 1 (i.e., the Mg-9wt.%Al alloy that has only been cleaned and dried in step (1)) is shown;
[0037] Figure 2 is the SEM metallographic structure diagram of the heat-treated sample in Example 1 (i.e., the sample obtained after the treatment in step (2));
[0038] Figure 3 The SEM microstructure images of the surface (a) and cross section (b) of the hydrothermally treated sample in Example 1 (i.e., the sample obtained after the treatment in step (3)) after the hydrothermal treatment with 0.01M sodium hydroxide solution;
[0039] Figure 4 The SEM microstructure images of the surface (a) and cross section (b) of the final sample obtained after the Mg-9wt.%Al alloy in Comparative Example 1 was directly subjected to hydrothermal treatment;
[0040] Figure 5 The SEM microstructure images of the surface (a) and cross section (b) of the final sample obtained in Comparative Example 2;
[0041] Figure 6 The SEM microstructure images of the surface (a) and cross section (b) of the final sample obtained in Comparative Example 3;
[0042] Figure 7 The XRD diagrams of the final samples obtained in Example 1 and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0044] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0048] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0049] All raw materials used in the examples of the present invention are commercially available.
[0050] The present invention is directed to Mg-9wt.%Al alloy, that is, a magnesium-aluminum alloy with an aluminum content of about 9wt.%. In an embodiment of the present invention, the Mg-9wt.%Al alloy is purchased from Yueyang Yuhua Metallurgical New Materials Co., Ltd.
[0051] In the embodiment of the present invention, after the magnesium-aluminum alloy is buried in the graphite powder, the amount of graphite powder used should be sufficient to cover the magnesium-aluminum alloy workpiece, and after compaction, a protective atmosphere can be formed to isolate oxygen in the air. The specific amount of graphite powder may need to be adjusted according to actual processing conditions and experience. In actual operation, it is sufficient to ensure that the amount of graphite powder used can effectively isolate the air and prevent the magnesium-aluminum alloy from oxidation.
[0052] The technical solution of the present invention is further illustrated by the following embodiments.
[0053] Example 1
[0054] This embodiment provides a method for homogenizing the thickness of a magnesium-aluminum alloy self-deformed hydrothermal film based on a precipitated phase hierarchical structure:
[0055] (1) Sample pretreatment:
[0056] 1) Cleaning: First, the Mg-9wt.%Al alloy (size: 10mm×10mm×4mm, the same below) was cleaned with soapy water to remove surface oil, then rinsed with deionized water, and finally ultrasonically cleaned in anhydrous ethanol for 5 minutes;
[0057] 2) Drying: Take the sample out of the anhydrous ethanol and blow dry it with cold air;
[0058] (2) Heat treatment:
[0059] First, the box furnace is heated to 410° C., and then the Mg-9wt.%Al alloy treated in step (1) is buried in a crucible containing graphite powder and compacted to isolate the air, and then placed in a box furnace for solution treatment, kept warm for 24 hours, taken out, and water-cooled; the sample after solution treatment is buried in graphite powder again, placed in a box furnace for aging treatment, the aging temperature is 300° C., the heat preservation time is 12 hours, and then water-cooled to achieve the purpose of adjusting the microstructure;
[0060] (3) Hydrothermal treatment:
[0061] 1) Grinding: The heat-treated Mg-9wt.%Al alloy was polished with 800#, 1200# and 2000# SiC sandpaper in turn to smooth the surface and eliminate the oxide layer formed by wire cutting and heat treatment;
[0062] 2) Cleaning: The polished Mg-9wt.%Al alloy was first rinsed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 5 minutes;
[0063] 3) Drying: Take out the Mg-9wt.%Al alloy from the anhydrous ethanol and dry it with cold air;
[0064] 4) Hydrothermal reaction: the prepared Mg-9wt.%Al alloy was placed in a polytetrafluoroethylene liner, 10 mL of 0.01M sodium hydroxide solution was added, sealed in a stainless steel hydrothermal kettle, placed in a blast drying oven, heated to 120°C and kept warm for 10 hours, and then taken out;
[0065] 5) Cleaning: First, rinse off the hydrothermal solution remaining on the surface with deionized water, and then rinse with anhydrous ethanol;
[0066] 6) Drying: Finally, use cold air to blow dry the anhydrous ethanol.
[0067] The surface and cross-sectional morphologies of the samples were observed using a scanning electron microscope (SEM); the phase composition of the samples was analyzed using an X-ray diffraction (XRD).
[0068] Figure 1 This is the SEM microstructure of the as-cast sample (i.e., the Mg-9wt.%Al alloy that has only been cleaned and dried in step (1)). It can be seen that its microstructure consists of two parts, one is the β phase with an island structure, with an average size of approximately 10 to 20 microns, and the other is the α matrix. Figure 2 The SEM microstructure diagram of the heat-treated sample (i.e., the sample obtained after the treatment in step (2)) shows that the original large island-shaped β phase has disappeared, and is replaced by a wide range of hierarchical β phases of various forms, including a lath-shaped β phase with a length of about 2.22±1.29 microns and a width of about 0.24±0.05 microns, a dot-shaped β phase with an average size of 0.51±0.11 microns, and a slightly larger pancake-shaped β phase with a size of 1.28±0.38 microns. These hierarchical second phases are the key to the uniform thickness of the self-stratified hydrothermal film.
[0069] Figure 3 The SEM microstructure diagram of the surface (a) and cross section (b) of the hydrothermal treated sample (i.e., the sample obtained after step (3)) after hydrothermal treatment with 0.01M sodium hydroxide solution. It can be found that after the heat-treated sample is hydrothermally treated with 0.01M sodium hydroxide solution, there is a LDH layer structure on the surface (combined with Figure 7 From the cross-sectional morphology, we can observe the hierarchical second phase under the membrane layer. The hydrothermal membrane has obvious self-decomposition phenomenon. The top layer is the LDH membrane layer, and the bottom layer is a uniform Mg(OH)2 dense layer with a thickness of 2.83±0.21 μm.
[0070] Comparative Example 1
[0071] (1) Sample pretreatment:
[0072] 1) Cleaning: First, the Mg-9wt.%Al alloy was cleaned with soapy water to remove surface oil, then rinsed with deionized water, and finally ultrasonically cleaned in anhydrous ethanol for 5 minutes;
[0073] 2) Drying: Take the sample out of the anhydrous ethanol and blow dry it with cold air;
[0074] (2) Hydrothermal treatment:
[0075] 1) Grinding: The Mg-9wt.%Al alloy treated in step (1) was grinded with 800#, 1200# and 2000# SiC sandpaper in sequence to smooth the surface;
[0076] 2) Cleaning: The polished Mg-9wt.%Al alloy was first rinsed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 5 minutes;
[0077] 3) Drying: Take out the Mg-9wt.%Al alloy from the anhydrous ethanol and dry it with cold air;
[0078] 4) Hydrothermal reaction: the prepared Mg-9wt.%Al alloy was placed in a polytetrafluoroethylene liner, 10 mL of 0.01M sodium hydroxide solution was added, sealed in a stainless steel hydrothermal kettle, placed in a blast drying oven, heated to 120°C and kept warm for 10 hours, and then taken out;
[0079] 5) Cleaning: First, rinse off the hydrothermal solution remaining on the surface with deionized water, and then rinse with anhydrous ethanol;
[0080] 6) Drying: Finally, use cold air to blow dry the anhydrous ethanol.
[0081] The surface (a) and cross-section (b) SEM microstructures of the sample obtained by direct hydrothermal treatment of the Mg-9wt.%Al alloy in this comparative example are shown in FIG. Figure 4 It can be found that after the Mg-9wt.%Al alloy is directly hydrothermally treated with 0.01M sodium hydroxide solution, LDH flakes are also generated on its surface, and the cross section is also a self-shaped layered structure, but the thickness of the dense layer on the island second phase (1.05±0.16 microns) is significantly different from the thickness of the dense layer on the substrate (2.92±0.11 microns). It proves that heat treatment can form a self-shaped layered hydrothermal film with uniform thickness, while direct hydrothermal treatment cannot form a self-shaped layered hydrothermal film with uniform thickness.
[0082] Comparative Example 2
[0083] Same as Example 1, except that the concentration of the sodium hydroxide solution during the hydrothermal treatment is 1M.
[0084] The SEM microstructures of the surface (a) and cross-section (b) of the sample obtained in this comparative example are shown in Figure 5 It can be seen that after the heat-treated sample was hydrothermally treated with 1M sodium hydroxide solution, there were some sparse small flakes on the surface. The XRD test results could not show the characteristic signal of LDH. The cross-sectional view also showed that there was only one dense layer, and there was no self-deformation stratification. In contrast, the thickness of the dense layer obtained after hydrothermal treatment with high-concentration sodium hydroxide solution (5.69±0.08 microns) was greater than that obtained with lower concentration.
[0085] Comparative Example 3
[0086] (1) Sample pretreatment:
[0087] 1) Cleaning: First, the Mg-9wt.%Al alloy was cleaned with soapy water to remove surface oil, then rinsed with deionized water, and finally ultrasonically cleaned in anhydrous ethanol for 5 minutes;
[0088] 2) Drying: Take the sample out of the anhydrous ethanol and blow dry it with cold air;
[0089] (2) Hydrothermal treatment:
[0090] 1) Grinding: The Mg-9wt.%Al alloy treated in step (1) was grinded with 800#, 1200# and 2000# SiC sandpaper in sequence to smooth the surface;
[0091] 2) Cleaning: The polished Mg-9wt.%Al alloy was first rinsed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 5 minutes;
[0092] 3) Drying: Take out the Mg-9wt.%Al alloy from the anhydrous ethanol and dry it with cold air;
[0093] 4) Hydrothermal reaction: the prepared Mg-9wt.%Al alloy was placed in a polytetrafluoroethylene liner, 10 mL of 1M sodium hydroxide solution was added, sealed in a stainless steel hydrothermal kettle, placed in a blast drying oven, heated to 120°C and kept warm for 10 hours, and then taken out;
[0094] 5) Cleaning: First, rinse off the hydrothermal solution remaining on the surface with deionized water, and then rinse with anhydrous ethanol;
[0095] 6) Drying: Finally, use cold air to blow dry the anhydrous ethanol.
[0096] The SEM microstructures of the surface (a) and cross-section (b) of the sample obtained in this comparative example are shown in Figure 6It can be seen that after the as-cast sample was hydrothermally treated with 1M sodium hydroxide solution, there were some small flakes on the surface of the as-cast sample, and the XRD test results did not show the characteristic signal of LDH. There was only one dense layer on the cross section, and there was no self-demixing phenomenon. The thickness of the dense layer (5.80±0.30 microns) was greater than the thickness obtained by hydrothermal treatment with low concentration sodium hydroxide, and the difference in thickness between the second phase and the hydrothermal film on the substrate was not obvious.
[0097] The XRD patterns of the final samples obtained in Example 1 and Comparative Examples 1 to 3 are shown in Figure 7 ,Depend on Figure 7 It can be seen that low concentration of sodium hydroxide hydrothermal treatment solution is the key to the formation of self-shaped stratified hydrothermal films.
[0098] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film, characterized in that: The following steps are involved: Pretreatment of magnesium-aluminum alloy; The pretreated magnesium-aluminum alloy is buried in graphite powder for solution treatment, and a first water cooling treatment is performed after the solution treatment is completed; The product after the first water cooling treatment is buried in graphite powder again for aging treatment, and a second water cooling treatment is performed after the aging treatment is completed; Grinding, cleaning and drying the product after the second water cooling treatment; A sodium hydroxide solution with a concentration of 0.01 M is added to the dried product for hydrothermal treatment, and the product after the hydrothermal treatment is cleaned and dried.
2. The method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film according to claim 1, characterized in that: The step of pre-treating the magnesium-aluminum alloy is: washing the magnesium-aluminum alloy with soap water, deionized water and anhydrous ethanol in sequence, and drying the magnesium-aluminum alloy.
3. The method for thickness homogenization of magnesium-aluminum alloy self-shaped layered hydrothermal film according to claim 1, characterized in that: The temperature of the isothermal solution treatment is 410° C., and the holding time is 24 hours.
4. The method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film according to claim 1, characterized in that: The temperature of the aging treatment is 300° C. and the insulation time is 12 hours.
5. The method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film according to claim 1, characterized in that: The grinding is performed by sequentially grinding with 800#, 1200# and 2000# SiC sandpapers.
6. The method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120° C. and the insulation time is 10 h.
7. The method for homogenizing the thickness of a magnesium-aluminum alloy self-shaped layered hydrothermal film according to claim 1, characterized in that: The drying is all cold air drying.
Citation Information
Patent Citations
Method for magnesium alloy in-situ growth LDH conversion film
CN108707889A
Method for one-step in-situ electro-deposition of layered double hydroxide coating on magnesium alloy surface
CN110484950A
Magnesium alloy composite material with magnesium-aluminum layered double hydroxide film layer and preparation method
CN117187805A